Metody consensusu w odniesieniu do hierarchicznych i ważonych niepełnych podziałów uporządkowanych - Hernes, Marcin; Sobieska-Karpińska, Jadwiga (Consensus Methods for Solving Conflicts in Hierarchical and Weight Incomplete Ordered Partitions, 2006)
The article presents consensus methods for solving conflicts in hierarchical and weight incomplete ordered partitions. The hierarchical and weight incomplete ordered partitions are an agent knowledge structure in many cases. The consensus methods are one of the methods for solving knowledge conflicts in distributed systems. The article presents a definition of the hierarchical and weight incomplete ordered partitions, transformation of the hierarchical and weight incomplete ordered partition in the other hierarchical and weight incomplete ordered partitions, definition of distance among incomplete ordered partitions and the algorithms of consensus methods for two different criteria.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 22-29